Analisis Pengaruh Intellectual Capital Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2015 - gina septiana (JURNAL PUNDI, 2018)
The objective of this research is to determine the influence of intellectual capital to the firm value of the banks listed on BEI with financial performance as an intervening variable. The independent variable applied in this study was the intellectual capital which was measured by value added intellectual coefficient (VAIC). The dependent variable in this study was the firm value is measured by using price to book value (PBV), while financial performance as an intervening variable is measured by using return on asset (ROA). The sample used in this study are 11 banking companies listed by the Indonesia Stock Exchange (IDX) within the period of 2010-2015. This study used a quantitative approach to testing hypotheses used the technique of path analysis. To examine the effect of mediation used sobel test. The finding shows that (1) intellectual capital has significant effect to financial performance. (2) intellectual capital does not have significant effect to the level of firm value. (3) financial performance has significant effect to the level of firm value. (4) sobel test result showed that financial performance mediate intellectual capital to the firm value.